Commissioning of the 1 PW experimental area at ELI-NP using a short focal parabolic mirror for proton acceleration - M. O. Cernaianu; P. Ghenuche; F. Rotaru; L. Tudor; O. Chalus; C. Gheorghiu; D. C. Popescu; M. Gugiu; S. Balascuta; A. Magureanu; M. Tataru; V. Horny; et al. (Matter and Radiation at Extremes)
High-power laser systems have opened new frontiers in scientific research and have revolutionized various scientific fields, offering unprecedented capabilities for understanding fundamental physics and allowing unique applications. This paper details the successful commissioning of the 1 PW experimental area at the Extreme Light Infrastructure–Nuclear Physics (ELI-NP) facility in Romania, using both of the available laser arms. The experimental setup featured a short focal parabolic mirror to accelerate protons through the target normal sheath acceleration mechanism. Detailed experiments were conducted using various metallic and diamond-like carbon targets to investigate the dependence of the proton acceleration on different laser parameters. Furthermore, the paper discusses the critical role of the laser temporal profile in optimizing proton acceleration, supported by hydrodynamic simulations that are correlated with experimental outcomes. The findings underscore the potential of the ELI-NP facility to advance research in laser–plasma physics and contribute significantly to high-energy physics applications. The results of this commissioning establish a strong foundation for experiments by future users.